2021
DOI: 10.1111/nhs.12842
|View full text |Cite
|
Sign up to set email alerts
|

Three learning modalities' impact on clinical judgment and perceptions in newly graduated registered nurses: A quasi‐experimental study

Abstract: Newly graduated registered nurses face numerous challenges stemming from high patient workload, complicated interpersonal relationships, and a lack of nursing competence, which can lead to transitional shocks. Clinical judgment and confidence are well‐known keys to successful role transitions for these nurses. Simulation training is proposed as a new modality for enhancing comprehensive clinical competence of nurses, but current evidence on the impact of different simulations on nurses' clinical judgment and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Virtual patient is a teaching modality for forming clinical judgment ( Montgomery, 2006 ). Some researchers found that clinical judgment skill of nurses was developed by using virtual stimulation ( Fogg et al, 2020 ; Luo et al, 2021 ). Critical thinking is a foundation for clinical judgment ( Lee and Park, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Virtual patient is a teaching modality for forming clinical judgment ( Montgomery, 2006 ). Some researchers found that clinical judgment skill of nurses was developed by using virtual stimulation ( Fogg et al, 2020 ; Luo et al, 2021 ). Critical thinking is a foundation for clinical judgment ( Lee and Park, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…O uso da simulação realística tem sido primordial como ferramenta de ensino em instituições e universidades de ensino da área da saúde. Os achados desta revisão evidenciam que a aplicação dessa metodologia de ensino demonstra-se benéfica por diversos fatores, como o desenvolvimento do raciocínio clínico, o amadurecimento comportamental e emocional e o aprimoramento de habilidades técnicas 14 .…”
Section: Discussionunclassified
“…(3) A model of the role of antecedent variables of work role transition competence was constructed based on the JDCS model and employee learning theory, providing a theoretical framework for subsequent research. Previous studies have only been sporadically focused on the role of competence in work role transition [7,63]. Furthermore, there is a lack of in-depth research on the mechanism of generating work role transition competence, and no logical relationship has been constructed between the antecedent and causal variables of work role transition competence.…”
Section: Theoretical Implicationsmentioning
confidence: 99%